Compared presentation, management and long-term outcomes after acute myocardial infraction in men and women <50 years of age. The FAST-MI programme. (25th November 2020) - Danchin, N; Puymirat, E; Eltchaninoff, H; Manzo-Silberman, S; Marchand, S; Bataille, V; Drouet, E; Naccache, N; Ferrieres, J; Schiele, F; Simon, T
Abstract: : The number of young women suffering acute myocardial infarction (AMI) is increasing. There are conflicting results on the prognostic impact of gender in young patients with AMI. The aim of the present study was to assess in-hospital and 5-year outcomes in men and women ≤50 years old admitted for AMI and participating in the FAST-MI programme. Methods: FAST-MI consists in one-month nationwide French surveys of patients admitted for a recent AMI, repeated every 5 years since 2005. We used the 2005, 2010 and 2015 data with up to 5-year follow-up, to describe baseline characteristics and outcomes according to gender in young patients. Of 13, 130 patients included, 1, 912 were ≤50 years old (335 women, 17.5%). Results: Men and women had a similar age (44±5 years), BMI, current smoking (72% vs 75%), diabetes, family history, prior history of CVD, GRACE score (104±22 vs 106±23), and LVEF (54±10%). LDL at admission was lower in women (127±46 vs 138±46 mg/dl). Women had a higher admission heart rate (81±19 vs 78±17 BPM) and lower systolic blood pressure (133±26 vs 136±25 mm Hg). Presenting AMI was STEMI in 63% in women vs 68% in men (P=0.08). All in-hospital complications except reinfarction (1.8 vs 0.6%, p<0.03) were similar in women and men; in-hospital death was 1.5% vs 0.8%, P=0.20. Coronary angiography was performed slightly less often (97.6% vs 99.0%, P=0.047) and more women had non-significant coronary artery disease (CAD) (13% vs 6%, P<0.001); PCI was less often used (74% vs 85.5%, P<0.001). At discharge, ESC guidelines-recommended medical treatment was less often prescribed in women (41% vs 53%, P<0.001), even in patients with significant CAD (46% vs 55%, P=0.004). Kaplan-Meier 5-year survival did not differ in women (94.7%) and men (95.2%), P=0.56 (Figure). The respective figures for hospital survivors were 96.1% and 96.0% (HR 1.00, 95% CI 0.52–1.91; HR adjusted on age, type of MI, previous history of CAD, presence of significant CAD, LVEF, Killip class and appropriate medications at discharge: 0.99, 95% CI 0.51–0.92). Similar results were found for the combined end-point of death, AMI or stroke. Conclusion: There were more similarities than differences between women and men who sustained an AMI at age ≤50 years. Women had lower LDL-c, lower haemoglobin, higher heart rate and lower blood pressure on admission. Non-significant CAD was more frequently found in women, who were less often treated with PCI and recommended medications at discharge. Five-year outcomes, however, did not differ according to gender. Funding Acknowledgement: Type of funding source: Private grant(s) and/or Sponsorship. Main funding source(s): Pfizer, MSD, AstraZeneca